INVESTMENT ATTRACTIVENESS OF ENTERPRISES - Davydenko , N.M. (The actual problems of regional economy development, 2017)
In the article the approaches to defining the essence of the concept of “investment attractiveness of enterprises” were analyzed. On the example of "Agrofirm Brusilov" depth analysis of the agricultural enterprises to evaluate of profitability, liquidity, solvency, financial stability, the timing of the return of invested funds and minimizing investment risks was conducted. To study methods of rating and system analysis were used. To justify the conditions of increasing investment attractiveness farms method of scoring was used. It was established as a result of the use of integrated evaluation of the financial position one can see problem aspects of financial position of the company and develop measures to enhance liquidity, solvency, identify potential for raising the efficiency of company and prevention of financial crisis. The analysis of financial position showed that the management of the enterprise doesn’t think about financial stability and solvency, does not understand the benefit of borrowed capital. Using research results in practice of agricultural enterprises allows us to give a real evaluation of investment attractiveness and justify ways to improve it.